Representational Completeness: A Legal Test for Performance Information Instruments, Applied to Police Records in Indonesia - Ferroka Putra Wathan; Didi Jhondiani; Rafsandi Dimbara (Mandub : Jurnal Politik, Sosial, Hukum dan Humaniora, 2026)
Article 19A(1) of Undang-Undang Nomor 5 Tahun 2026 makes police performance accountability a statutory duty, requiring professionalism, proportionality, transparency, and accountability. Although this duty is implemented through reporting instruments, no legal standard defines when such instruments are insufficient. This article addresses that gap by constructing a doctrinal benchmark. Three criteria of representational completeness—functional, temporal, and structural—are derived from the duty of due care in Article 10(1)(d) of Undang-Undang Nomor 30 Tahun 2014, three components of Peraturan Presiden Nomor 29 Tahun 2014, and three administrative court rulings restated as duties of office. Each criterion is operationalized through an indicator observable directly from the reporting instrument. The framework is tested doctrinally and empirically using crime and clearance records from one district police command and two subordinate sector commands in South Sumatra (2022–2025), supported by eight service-chain interviews. The assessment targets the reporting instrument rather than organizational performance. All three indicators reveal deficiencies: no field links crime records with the preventive-work reporting regime; 139 offences recorded over ten months are presented as annual figures without distinguishing absent events from absent entries; and subordinate totals exceed superordinate totals (51 versus 43; 10 versus 3) without any statement of reporting scope. As these deficiencies arise from the reporting artefact itself, additional personnel or funding cannot resolve them. The appropriate remedy is regulatory anchoring de lege lata, and the criteria are transferable to any public agency reporting through aggregate data.